Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1186/s12882-017-0671-x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of new onset of end stage renal disease in Chinese patients with type 2 diabetes mellitus – a population-based retrospective cohort study

Abstract: BackgroundSince diabetes mellitus (DM) is the leading cause of end stage renal disease (ESRD), this study aimed to develop a 5-year ESRD risk prediction model among Chinese patients with Type 2 DM (T2DM) in primary care.MethodsA retrospective cohort study was conducted on 149,333 Chinese adult T2DM primary care patients without ESRD in 2010. Using the derivation cohort over a median of 5 years follow-up, the gender-specific models including the interaction effect between predictors and age were derived using C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
69
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(74 citation statements)
references
References 39 publications
(34 reference statements)
2
69
0
Order By: Relevance
“…Previously, human aortic smooth muscle cells were cultured in hyperglycemic and hyperphosphatemic media, and the combined effects of hyperphosphatemia and hyperglycemia were also observed on human aortic smooth muscle cell calcification (34). Regarding the above-mentioned results, it was concluded that there were combined effects of hyperglycemia and hyperphosphatemia on VSMC calcification, and it is considered to be a key explanation for why ESRD patients with diabetes mellitus exhibted shorter survival times/higher mortality rate (3537). In addition, it was noticed that calcification in 30 mM glucose (HG) was more significant than in 2.5 mM Pi.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, human aortic smooth muscle cells were cultured in hyperglycemic and hyperphosphatemic media, and the combined effects of hyperphosphatemia and hyperglycemia were also observed on human aortic smooth muscle cell calcification (34). Regarding the above-mentioned results, it was concluded that there were combined effects of hyperglycemia and hyperphosphatemia on VSMC calcification, and it is considered to be a key explanation for why ESRD patients with diabetes mellitus exhibted shorter survival times/higher mortality rate (3537). In addition, it was noticed that calcification in 30 mM glucose (HG) was more significant than in 2.5 mM Pi.…”
Section: Discussionmentioning
confidence: 99%
“…Prediction models for ESRD have been evaluated in patients with various pathologic conditions, such as CKD, [2326] light chain amyloidosis, [27] and diabetes. [2831] Nevertheless, an ESRD-prediction model after CABG has never been developed. The Cleveland Clinic score and the Society of Thoracic Surgery risk score have a limitation in predicting a risk of ESRD over several years.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear what occurs when hyperphosphatemia and hyperglycemia are present at the same time; however, these are likely to be the conditions that occur in patients with diabetic kidney disease (DKD) (17). It is well established that CKD patients with hyperglycemia have a shorter survival time and/or higher mortality rate (21,22). Yoshida et al (23) incubated rat and human aortic SMCs with various concentrations of phosphate and glucose, and demonstrated that calcium accumulation is increased by high phosphate concentration in a dose-dependent manner, but not by high glucose concentration.…”
Section: Discussionmentioning
confidence: 99%